How Discussion Works_outline for orientation session - Schmidli, Laura; Jabaily, Matthew; Wheeler, Diana (My University, 2009)
Overview of How Discussion participation and grading work in EPD 151. 2009-2010.
Keywords: Discussion criteria; Discussion ground rules; EPD; EPD 151